(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Background: A definitive treatment of SARS CoV-2 is yet to arrive and the human death toll rises exponentially globally. In this health emergency, it might be useful to look into the old therapies which could be effective against the virus. In vitro research showed Ivermectin could decrease the concentration of coronavirus 4000 to 5000 folds in living lung tissue. Aim: In this prospective study a combination of Ivermectin and Doxycycline will be evaluated therapeutically to treat COVID-19 patients. Methods: 100 COVID-19 patients were enrolled in this study with a predefined inclusion and exclusion criteria. RT- PCR of the SERS-CoV-2 will be done at designated government hospitals. The clinical features and response to treatment were noted according to a dedicated protocol. Results: In this study male and female were 64 and 36 respectively, the age ranged between 8 to 84 years. Retesting was done between 4 and 18 days of starting medication. All patients tested negative and their symptoms improved within 72 hours. There were no noticeable side effects. Conclusion: Combination of Ivermectin and doxycycline was found to be very effective in viral clearance in mild and moderately sick COVID-19 patients. Medical societies and institutions should undertake larger multi center studies to validate and recommend this combination therapy to include in national guidelines. J Bangladesh Coll Phys Surg 2020; 38(0): 10-15